STM study of exfoliated few layer black phosphorus annealed in ultrahigh vacuum. (22nd October 2018) - Kumar, Abhishek; Telesio, F; Forti, S; Al-Temimy, A; Coletti, C; Serrano-Ruiz, M; Caporali, M; Peruzzini, M; Beltram, F; Heun, S
Abstract: Black phosphorus (bP) has emerged as an interesting addition to the category of two-dimensional materials. Surface-science studies on this material are of great interest, but they are hampered by bP's high reactivity to oxygen and water, a major challenge to scanning tunneling microscopy (STM) experiments. As a consequence, the large majority of these studies were performed by cleaving a bulk crystal in situ . Here we present a study of surface modifications on exfoliated bP flakes upon consecutive annealing steps, up to 550 °C, well above the sublimation temperature of bP. In particular, our attention is focused on the temperature range 375 °C–400 °C, when sublimation starts, and a controlled desorption from the surface occurs alongside with the formation of characteristic well-aligned craters. There is an open debate in the literature about the crystallographic orientation of these craters, whether they align along the zigzag or the armchair direction. Thanks to the atomic resolution provided by STM, we are able to identify the orientation of the craters with respect to the bP crystal: the long axis of the craters is aligned along the zigzag direction of bP. This allows us to solve the controversy, and, moreover, to provide insight in the underlying desorption mechanism leading to crater formation.